Implementation of Human Resource Management at SMAIT Al-Fityan School Gowa, Gowa Regency - Idris Amiruddin; Misykat Malik Ibrahim; Mardhiah Mardhiah (Journal of Pedagogi, 2024)
This study aims to analyze the planning, implementation, and supervision of Human Resource Management (HRM) at SMAIT Al-Fityan School Gowa, Gowa Regency. A qualitative approach with phenomenological methods is used to collect data through interviews, observations, and documentation from related parties. The results of the study show that MSDM planning involves several stages, such as recruitment through meetings, distribution of pamphlets, file collection, interviews, probationary periods, and announcements. The selection is carried out in two stages: administration and interview. Orientation lasts from a probationary period to basic and advanced training for six months. The placement of educators is adjusted to their expertise in teaching, communicating, mastering technology, and management. Training and development are divided into general and religious training. The implementation of MSDM in this school runs systematically and structured, especially in recruitment, selection, orientation, placement, as well as training and development of educators. Supervision is carried out by school principals, directors, education offices, and international supervisors (intertek). The implication of this study is the importance of more attention from the foundation, especially on continuous professional training and development, to improve competence and innovation in teaching methods. Thus, educators can increase competence, job satisfaction, and better career development opportunities